1975
DOI: 10.2134/jeq1975.00472425000400030021x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Translocation of Sulfur Dioxide by Seedlings of Four Forest Tree Species

Abstract: Rates of absorption of SO2 and of translocation of absorbed sulfur were determined in sugar maple (Acer saccharum Marsh.), bigtooth aspen (Populus grandidentata Michx.), white ash (Fraxinus americana L.), and yellow birch seedlings [Betula alleghaniensis Britton (Betula lutea Michx. f.)]. Bigtooth aspen, a sensitive species, had the highest absorption rate with no prefumigation and sugar maple, a tolerant species, had the lowest. After 20 hours or more of prefumigation with 1,965 µg/m3 (0.75 ppm) SO2, the rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Leaves with greater leaf conductance would have an ability to absorb a larger amount of the toxicant through their stomata. Similar results correlating uptake with sensitivity to SO.^ or NO^ have also been reported for many species or cultivars (Jensen & Kozlowski, 1975;Bressan, Wilson & Filner, 1978;Caput et al, 1978;Furukavva et al, 1980;Elkiey & Ormrod, 1981 ;Okano, Machida & Totsuka, 1988;. In the case of PAN, however, Taylor et al (1961) found that pinto bean plants exposed to high concentrations for a short period in darkness exhibited no foliar injury, although the stomata were still open during the fumigation.…”
Section: Introductionsupporting
confidence: 66%
“…Leaves with greater leaf conductance would have an ability to absorb a larger amount of the toxicant through their stomata. Similar results correlating uptake with sensitivity to SO.^ or NO^ have also been reported for many species or cultivars (Jensen & Kozlowski, 1975;Bressan, Wilson & Filner, 1978;Caput et al, 1978;Furukavva et al, 1980;Elkiey & Ormrod, 1981 ;Okano, Machida & Totsuka, 1988;. In the case of PAN, however, Taylor et al (1961) found that pinto bean plants exposed to high concentrations for a short period in darkness exhibited no foliar injury, although the stomata were still open during the fumigation.…”
Section: Introductionsupporting
confidence: 66%
“…Photosynthesis is, in fact, one of the foremost processes to be affected by Cd treatment (Wang et al 2009). The decline in photosynthesis can be attributed to low stomatal conductance as was observed in Acer leaves, which have small stomatal apertures (Jensen & Kozlowski 1975). The rate of photosynthesis may also be affected by damage to the electron transport system (Ishibashi et al 1997), or by a decrease in PEP activity and concentration as a result of hydrolysis and mobilisation from leaves (Joshi et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they can cause lesions on the leaf surface and a decrease in plant productivity, thus decreasing the capacity of the plants to act as sinks for these pollutants. The absorption rates of 0 3 (Turner et al 1972;Thorne and Hanson 1976), S02 (Jensen and Kozlowski 1975;Bressan et al 1978;Caput et al 1978;Furukawa et al 1980), and N02 (Okano et al 1988(Okano et al , 1989 have,in many species and cultivars, been reported to correlate with their susceptibility to the pollutant.…”
Section: Stomatal Control Of Gas Absorption and Susceptibility Of Plamentioning
confidence: 99%